Improving Bambara Groundnut Production: Insight Into the Role of Omics and Beneficial Bacteria - Ajilogba, Caroline Fadeke; Olanrewaju, Oluwaseyi Samuel; Babalola, Olubukola Oluranti (Frontiers in Plant Science, 2022)
With the rise in the world population, environmental hazards caused by chemical fertilizers, and a decrease in food supply due to global climate change, food security has become very pertinent. In addition, considerable parts of agriculture lands have been lost to urbanization. It has therefore been projected that at the present rate of population increase coupled with the other mentioned factors, available food will not be enough to feed the world. Hence, drastic approach is needed to improve agriculture output as well as human sustainability. Application of environmentally-sustainable approach; such as the use of beneficial microbes, and improved breeding of underutilized legumes are one of the proposed sustainable ways of achieving food security. Microbiome-assisted breeding in underutilized legumes is an untapped area with great capabilities to improve food security. Furthermore, revolution in genomics-adaptation to crop improvement has changed the approach from conventional breeding to more advanced genomic-assisted breeding on the host plant and its microbiome. The use of rhizobacteria is very important to improving crop yield, especially rhizobacteria from legumes like Bambara groundnut (BGN). BGN is an important legume in sub-Saharan Africa with high ability to tolerate drought and thrive well in marginalized soils. BGN and its interaction with various rhizobacteria in the soil could play a vital role in crop production and protection. This review focus on the importance of genomics application to BGN and its microbiome with the view of setting a potential blueprint for improved BGN breeding through integration of beneficial bacteria.